Hematopoietic stem cell transplantation in patients with gain-of-function signal transducer and activator of transcription 1 mutations - Leiding, Jennifer W.; Okada, Satoshi; Hagin, David; Abinun, Mario; Shcherbina, Anna; Balashov, Dmitry N.; Kim, Vy H.D.; Ovadia, Adi; Guthery, Stephen L.; Pulsipher, Michael; Lilic, Desa; Devlin, Lisa A.; et al. (Journal of allergy and clinical immunology, 2018)
Gain-of-function (GOF) mutations in signal transducer and activator of transcription 1 (STAT1) cause susceptibility to a range of infections, autoimmunity, immune dysregulation, and combined immunodeficiency. Disease manifestations can be mild or severe and life-threatening. Hematopoietic stem cell transplantation (HSCT) has been used in some patients with more severe symptoms to treat and cure the disorder. However, the outcome of HSCT for this disorder is not well established. We sought to aggregate the worldwide experience of HSCT in patients with GOF-STAT1 mutations and to assess outcomes, including donor engraftment, overall survival, graft-versus-host disease, and transplant-related complications. Data were collected from an international cohort of 15 patients with GOF-STAT1 mutations who had undergone HSCT using a variety of conditioning regimens and donor sources. Retrospective data collection allowed the outcome of transplantation to be assessed. In vitro functional testing was performed to confirm that each of the identified STAT1 variants was in fact a GOF mutation. Primary donor engraftment in this cohort of 15 patients with GOF-STAT1 mutations was 74%, and overall survival was only 40%. Secondary graft failure was common (50%), and posttransplantation event-free survival was poor (10% by 100 days). A subset of patients had hemophagocytic lymphohistiocytosis before transplant, contributing to their poor outcomes. Our data indicate that HSCT for patients with GOF-STAT1 mutations is curative but has significant risk of secondary graft failure and death.